2018
DOI: 10.1002/ecs2.2526
|View full text |Cite
|
Sign up to set email alerts
|

Root endophytes and invasiveness: no difference between native and non‐native Phragmites in the Great Lakes Region

Abstract: Microbial interactions could play an important role in plant invasions. If invasive plants associate with relatively more mutualists or fewer pathogens than their native counterparts, then microbial communities could foster plant invasiveness. Studies examining the effects of microbes on invasive plants commonly focus on a single microbial group (e.g., bacteria) or measure only plant response to microbes, not documenting the specific taxa associating with invaders. We surveyed root microbial communities associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 47 publications
(84 reference statements)
10
28
1
Order By: Relevance
“…2 ), even though most taxa were present in both lineages and half of them were found at all sites. These results differ from those reported by Bickford et al [ 79 ] who found no differences in root fungal endophytes between P. australis lineages in the Great Lakes, USA. However, soil saturation was a relevant environmental factor in that study, whereas water level did not appear to play a role in endophyte colonization or community structure in our study sites (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…2 ), even though most taxa were present in both lineages and half of them were found at all sites. These results differ from those reported by Bickford et al [ 79 ] who found no differences in root fungal endophytes between P. australis lineages in the Great Lakes, USA. However, soil saturation was a relevant environmental factor in that study, whereas water level did not appear to play a role in endophyte colonization or community structure in our study sites (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…We expand on these earlier findings as one of the first studies conducted outside an agricultural context, by comparing closely related native and invasive taxa over a broad geographical scale and quantifying damage from the fungal pathogen community. For Phragmites , the divergent fungal communities for all lineage comparisons indicate a high degree of specialization of plant–fungal interactions at the lineage level, consistent with previous findings comparing rhizosphere oomycete (Crocker et al, 2015; Nelson & Karp, 2013), bacterial (Bowen et al, 2017) and archaean (Yarwood et al, 2016) communities among Phragmites lineages, but contrasting with a recent study of endophytic root fungal, bacterial and oomycete communities in the Great Lakes region (Bickford et al, 2018). However, our study is the first to examine differences among Phragmites lineages in their foliar microbiome, where leaf tissue provides a substrate different from that of roots or the rhizosphere, which varies among Phragmites lineages in leaf chemistry (Cronin et al, 2015; Pyšek et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…Our results from the field survey and common garden experiment present contrasting evidence for our first prediction and the enemy release hypothesis. Despite divergent foliar fungal communities and pathogen abundance, pathogen damage did not differ among Phragmites lineages in the field, suggesting that release from fungal pathogens does not contribute to the success of invasion by the European lineage (Bickford et al, 2018). However, the common garden experiment identified genetically based differences in susceptibility to some putative pathogens that favoured the European lineage over the Gulf and native lineages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where we also found no differences between Phragmites lineages across three major microbial groups (Bickford et al, 2018). In exploration of the root microbiome, Bickford et al 2018 The functional implication of this dissimilarity is unresolved in regard to invasive capacity.…”
Section: Discussionmentioning
confidence: 44%